KETERAMPILAN MENULIS PANTUN MELALUI KUIS ”BBM” (BERMAIN DENGAN BINTANG DAN METEOR) DI SMA NEGERI 7 YOGYAKARTA - Agriyati Agriyati (Dinas Pendidikan, Pemuda dan Olahraga DIY, 2018)
This study describes a learning innovations that generally aims to optimize the student skill in writing or producing text of the pantun. Specifically, the aims of this study were (1) to find an interesting appraisal model by applying quiz game, (2) to find the latest assessment model that was not boring, as well as able to made the student more active, enthusiastic, happy and vibrant, (3) to emerge the student’s interest in writing the pantun, which recently miswriting and contravene the requirement of the pantun writing. As writing is considered as one of four most difficult language skills both by students and teachers, this learning innovation is needed to create a learning system or model, as well as an attractive assessment model that promotes student activity. Therefore, "BBM" (Bermain dengan Bintang dan Meteor) quiz becomes a priority to overcome the low ability of writing / producing texts of the pantun among student of class XI SMA Negeri 7 Yogyakarta. This "BBM" quiz was a form of game that offers star and meteor for student (participants/groups) for each time they answering questions. The correct answer gets a star. On the contrary, the false answer gets a meteor. The star score was ten (10) and the meteor score was zero (0). The star or meteor is mounted on the panel board. Stars that form vertical, horizontal, and diagonal patterns on the panel board will get a bonus of 100 perfect values. The star cannot be removed, but the meteor can be removed. Result of this study shows that this learning innovation was able to create a fun and varied learning, the student were more motivated, enthusiastic, and more active in attending the learning. This result is expected to optimize the student’s writing ability, especially in writing of the pantun.